The Irish perspective on placement opportunities accessed by students on undergraduate Nursing (Intellectual Disability) programmes: A quantitative descriptive study. (15th March 2022) - Carey, Eileen; Foran, Sinéad; Burke, Geraldine; Ryan, Judy
Abstract: Background: Globally there are few countries facilitating undergraduate programmes to train nurses specifically to support people with intellectual disabilities. In Ireland, eight Higher Education Institutions (HEIs) in partnership with associated health care providers (AHCPs) facilitate undergraduate Nursing (Intellectual Disability) degree programmes. Practice placements are a core element of these programmes whereby students complete several hours in these learning environments as part fulfilment of their degree requirements. Because people with intellectual disability who traditionally accessed services in congregated settings, are now increasingly accessing mainstream services, new placement types are emerging. This study aimed to describe practice placements, areas of the registered nurse in intellectual disability (RNID) specialist support and other learning opportunities accessed by undergraduate students on Bachelor of Science Nursing (Intellectual Disability) programmes across eight HEIs in Ireland. Methods: A survey design involving a Placement Opportunities Tool (POT) developed through expert group meetings and consensus was utilised. Following ethical approval, Qualtrics XM software was enlisted to distribute the online survey to eight HEIs in Ireland. Excel and SPSS were engaged to undertake descriptive statistical analysis. Findings: A total of five fully complete and one partially complete POT were included in the data analysis. Findings demonstrate that majority of placements are accessed in traditional Intellectual Disability services with students having less access to placements either in mainstream services or with RNID specialists. Conclusions: This study details placement accessed by nursing students (Intellectual Disability) and associated areas of RNID specialist support. There is an urgent need to develop undergraduate student placements which reflect the contemporary lives of people with an intellectual disability. HEIs, AHCPs, nursing regulators, support persons and people with intellectual disabilities need to collaborate to develop practice placements enabling students to access learning experiences embedded in the realities of people living with intellectual disability who are integrating into their communities. Accessible summary: Nursing students (Intellectual Disability) learn in higher education institutions and in a range of places where people with intellectual disability get support. We wanted to find out about the different places nursing students go to, to support people with intellectual disability as part of their learning. We found students go most often to intellectual disability services and less often to placements in mainstream settings or with registered nurse in intellectual disability specialists. Everyone needs to work together to make sure students get access to placements where they can learn how to best support people with intellectual disability.